Osnovnye napravleniya sovershenstvovoaniya professional'noi podgotovki studentov IFK, spetsializiruyushchikhsya vidam bor'by i vostochnykh edinobortsv (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of the present study was to consider the main directions to improve the professional training of physical culture higher educational institutions` students, specializing on the kinds of wrestling and the eastern single-combats. The first direction is the change of the educational content with a help of the revealation of the future profession`s demands and the integration of scientific knowledges and the data of a social practice. The second direction is dedicated to the improvement of metods for the educational material`s on a competitive activities; mastering and transformation and to the formation of intentions and attitudes.